A implantação da gestão de resíduos sólidos na central de abastecimento - Empasa João Pessoa-PB: avaliação da efetividade do PGIRS - Santos, Silvana Alves dos (2019)
The biggest challenge today is the management of solid waste in the country, especially about the final disposal. The supply centers in Brazil develop several activities aimed at the commercialization of fruits and vegetables, generating a daily production of sudden vacations, which generate poor management, causing great waste. The recent implementation of Solid Waste Management Plans (PGIRS) in several supply centers aiming at the control of waste management requires a follow up of their actions to evaluate the effectiveness of these plans, analyzing internal results in the plants, as well as in the environment. Thus, the objective of this work was to reconstitute the PGIRS implementation process in 2015 at the Supply Center EMPASA/JP, starting as a starting point for waste management actions initiated in 2010. The research was conducted in the evaluation period from 2010 to 2018 as an action research through the participation in the management actions of organic and recyclable waste contemplated by the company's PGIRS, along with a team composed of internal employees and researchers from public universities. Awareness-raising actions were carried out with outsourced merchants and cleaning agents and partnerships were established with other federal, state and private institutions to assist in the improvement of the work carried out at EMPASA through academic research. As a result, a change in the conscience of the traders and employees of the central of supply, where they emphasized the importance of the correct destination of the residues in the public health of the own work environment, with elimination of the sanitary problems caused by the accumulation of the residues in the internal area of the central supply. Therefore, the research demonstrated the effectiveness of the implementation of PGIRS in the EMPASA / CEASA-JP Supply Center, with the reduction of the waste load destined to the sanitary landfill of João Pessoa and consequently of the negative effects on the environment, as well as change of habits of employees and traders.